NEW RADIOLARIAN SPECIES FROM THE UPPER CRETACEOUS NAIBA REFERENCE SECTION (SOUTHERN SAKHALIN) - Bragina L.G. (My University, 2003)
A new study of the Late Cretaceous radiolarian assemblages of southern Sakhalin has revealed a large number of new taxa. The species Cenosphaera robusta sp. nov., Hexapyramis (?) perforatum sp. nov., Patellula sakhalinica sp. nov., Spongodiscus sakhalinensis sp. nov., S. quasipersenex sp. nov., S. concentricus sp. nov., Spongurus cylindricus sp. nov., Stylodruppa ornata sp. nov., and Patulibracchium (?) quadroastrum sp. nov. are described.
Keywords: Radiolaria; Upper Cretaceous; Sakhalin; Mesozoic::Cretaceous; Мезозой::Меловая